As representações sociais de pacientes em ínicio de terapia anti-retroviral envolvidas na adesão ao tratamento - Angela de Cassia Rover da Silva (2006)
This study aimed to understand the Social Representations of HIV or AIDS virus about the aspects that are connected to the adherence to the antiretroviral therapy. 30 open interviews were analyzed, achieved with patients in beginning of antiretroviral therapy, attended in 30 reference services in Belo Horizonte, Minas Gerais. From the analysis it emerged categories related to the adherence that form two great groups. The first includes the aspects related to the experience of the treatment itself, constituted by: a) the side effects of the medicines; b) the explicitness about the objectives of the treatment; c) the information (knowledge) about HIV, aids and ARV; d) The visibility of the symptom control of the aids and opportunist diseases; and e) the expected prospects with the treatment. The categories related to the social experience of the disease and of its treatment are in the second group, integrated by: a) interactions with the family; b) relationship with the partner; c) presence of everyday friends; d) the relationship with the health crew; e) the importance of the work; f) the experience of the secret around the disease and the treatment: prejudice and dissimulation; g) the faith and the religiosity as support for facing the disease and the treatment; h) the importance of the wish and will power; and i) the necessary changes for facing the disease and the treatment. The interpretation of the information evidenced that the main social representations related to the adherence are the aids as death, which can be postponed with the regular use of antiretroviral treatment. The medicines are represented as a possibility of keeping the patient alive (and not dying) while the aids cure comes. Stigma and prejudice are still representations that surround the relations with the family, the friends, the partners, the health crew and the work, objectified by the choice of the secret around the serology and the dissimulation of the medication usage.